Policy and Solid Waste Management in Natal / Brazil (Revista LIDER, 2020)
This article analyzes the current policy of solid waste management in the city of Natal, Brazil. It is the result of a doctoral research finished in 2010, and a research project started in 2013 on recycling inNatal. The results summarize information collected from interviewswith recyclable material separators and public managers of Natal and other sources and official information given. In Natal, the Municipality has been using elements of socio-environmental speech to justify the economic actions of its waste management, according with the Brazilian political axes for residues. This practice is configured as an official economic environmentalism, which strives to ensure the reproduction modelof final waste through the use of socio environmental discourse